American bioethics : crossing human rights and health law boundaries - Annas, George J. (Oxford University Press, 2005)
Bioethics was "born in the USA" and the values American bioethics embrace are based on American law, including liberty and justice. This book crosses the borders between bioethics and law, but moves beyond the domestic law/bioethics struggles for dominance by exploring attempts to articulate universal principles based on international human rights. The isolationism of bioethics in the US is not tenable in the wake of scientific triumphs like decoding the human genome, and civilizational tragedies like international terrorism. Annas argues that by crossing boundaries, which have artificially separated bioethics and health law from the international human rights movement, American bioethics can be reborn as a global force for good, instead of serving mainly the purposes of U.S. academics. This thesis is explored in a variety of international contexts such as, terrorism and genetic engineering, and in U.S. domestic disputes such as, patient rights and market medicine. The citizens of the world have created two universal codes: science has sequenced the human genome and the United Nations has produced the Universal Declaration of Human Rights.; The challenge for American bioethics is to combine these two great codes in imaginative and constructive ways to make the world a better, and healthier, place to live.